Unified picture of vibrational relaxation of OH stretch at the air/water interface - Woongmo Sung; Ken-ichi Inoue; Satoshi Nihonyanagi; Tahei Tahara (Nature Communications, 2024)
Abstract The elucidation of the energy dissipation process is crucial for understanding various phenomena occurring in nature. Yet, the vibrational relaxation and its timescale at the water interface, where the hydrogen-bonding network is truncated, are not well understood and are still under debate. In the present study, we focus on the OH stretch of interfacial water at the air/water interface and investigate its vibrational relaxation by femtosecond time-resolved, heterodyne-detected vibrational sum-frequency generation (TR-HD-VSFG) spectroscopy. The temporal change of the vibrationally excited hydrogen-bonded (HB) OH stretch band (ν=1→2 transition) is measured, enabling us to determine reliable vibrational relaxation (T1) time. The T1 times obtained with direct excitations of HB OH stretch are 0.2-0.4 ps, which are similar to the T1 time in bulk water and do not noticeably change with the excitation frequency. It suggests that vibrational relaxation of the interfacial HB OH proceeds predominantly with the intramolecular relaxation mechanism as in the case of bulk water. The delayed rise and following decay of the excited-state HB OH band are observed with excitation of free OH stretch, indicating conversion from excited free OH to excited HB OH (~0.9 ps) followed by relaxation to low-frequency vibrations (~0.3 ps). This study provides a complete set of the T1 time of the interfacial OH stretch and presents a unified picture of its vibrational relaxation at the air/water interface.